PENGARUH FASILITAS TAX AMNESTY PERIODE I-II TERHADAP KEPATUHAN WAJIB PAJAK (STUDI KASUS PADA MAHASISWA PERGURUAN TINGGI ISLAM DI MALANG) - Avi Rizqi Rahayu Putri; Afifudin Afifudin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
In general, Tax Amnesty  is a limited time opportunity for the same group of taxpayers as the pardon of tax liabilities relating to the past. The purpose of this research is to know and analyze Amnesty facility of I-II period on Taxpayer compliance. The population in this study is all faculty of economics who have taken the subject of taxation registered in Student Islamic University of Malang. Sampling technique through simple random sampling method or random selection. From hypothesis testing simultaneously can be seen simultaneously significant facility of tax amnesty period I-II to taxpayer compliance. Analysis test using a model simple linier regresion analysis. The result of this study concluded that tax amnesty has positive and significant effect to an taxpayer compliance.